Insulin: Trigger and Target of Renal Functions - Pina, Ana F.; Borges, Diego O.; Meneses, Maria João; Branco, Patrícia; Birne, Rita; Vilasi, Antonio; Macedo, Maria Paula (Frontiers in Cell and Developmental Biology, 2020)
Kidney function in metabolism is often underestimated. Although the word “clearance” is associated to “degradation”, at nephron level, a proper balance between what is truly degraded and what is redirected to de novo utilization is crucial for the maintenance of electrolytic and acid-basic balance and energy conservation. Insulin is probably one of the best examples of how diverse and heterogeneous kidney response can be. Kidney has a primary role in the degradation of insulin released in the bloodstream, but it is also incredibly susceptible to insulin action throughout the nephron. Fluctuations in insulin levels during fast and fed state add another layer of complexity in the understanding of kidney fine-tuning. This review aims at revisiting renal insulin actions and clearance and to address the association of kidney dysmetabolism with hyperinsulinemia and insulin resistance, both highly prevalent phenomena in modern society.